Tumour radiosensitivity is associated with immune activation in solid tumours. (October 2017) - Strom, Tobin; Harrison, Louis B.; Giuliano, Anna R.; Schell, Michael J.; Eschrich, Steven A.; Berglund, Anders; Fulp, William; Thapa, Ram; Coppola, Domenico; Kim, Sungjune; Frakes, Jessica; Foekens, John; et al.
Abstract: Purpose: Our goal was to determine whether tumour radiosensitivity is associated with activation of the immune system across all tumour types as measured by two gene expression signatures (GESs). Methods: We identified 10, 240 genomically profiled distinct solid primary tumours with gene expression analysis available from an institutional de-identified database. Two separate GESs were included in the analysis, the radiosensitivity index (RSI) GES (a 10-gene GES as a measure of radiosensitivity) and the 12-chemokine (12-CK) signature (a 12-gene GES as a measure of immune activation). We tested whether the RSI and 12-CK were associated with each other across all tumour samples and, in an exploratory analysis, their prognostic significance in predicting distant metastasis-free survival (DMFS) among a well-characterised, independent cohort of 282 early-stage breast cancer cases treated with surgery and post-operative radiation alone without systemic therapy. The lower the RSI score, the higher the tumour radiosensitivity; whereas, the higher the 12-CK score the higher the immune activation. Results: Using an RSI cut-point of ≤0.3745, RSI-low tumours (n = 4, 291, 41.9%) had a significantly higher median 12-CK GES value (0.54 [−0.136, 1.095]) compared with RSI-high tumours (−0.17 [–0.82, 0.42]; p < 0.001) across all tumour samples, indicating that radiosensitivity is associated with immune activation. In an exploratory analysis of early-stage breast cancer cases, a multivariable model with patient age, RSI and 12-CK provided a strong composite model for DMFS (p = 0.02), with RSI (hazard ratio [HR] 0.63 [95% confidence interval 0.36, 1.09]) and 12-CK (HR 0.66 [0.41, 1.04]) each providing comparable contributions. Conclusions: Tumour radiosensitivity is associated with immune activation as measured by the two GESs. Highlights: There are data that suggest an interplay between response to radiation therapy and immune activation. If a gene expression signature (GES) could improve the identification of this interplay it would likely be deemed a success. We compared two GES for tumour radiosensitivity index (RSI) and immune activation (12-CK). RSI and 12-CK GES are associated across all tumour types. The combined RSI and 12-CK GES phenotype has the potential to improve our prognostic ability.